2020
DOI: 10.3991/ijim.v14i01.11337
|View full text |Cite
|
Sign up to set email alerts
|

VR Use in Online Learning for Higher Education in Indonesia

Abstract: <p>This research leads to the object of learning in network-based learning programs application of the use of VR in online learning for students in Higher EducationThis research is located in the Education Technology study program, Universitas Negeri Jakarta, Indonesia. This study focuses on learning theories, learning methods and learning models used in technology to improve learning outcomes in class. This method used explanatory sequential mixed methods research. Field trials were conducted for studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 24 publications
1
27
0
4
Order By: Relevance
“…The advancement in computer technology has led to the application of software development in learning [1]- [3]. This further motivates teachers to take steps to integrate computers into the educational environment [4], [5], in order to improve the effectiveness and quality of the education system [6]- [8]. This development also provides additional training and opportunities for students to explore their problemsolving attributes by seeking alternative solutions due to the unlimited computer use capabilities in the learning [9]- [11].…”
Section: Introductionmentioning
confidence: 99%
“…The advancement in computer technology has led to the application of software development in learning [1]- [3]. This further motivates teachers to take steps to integrate computers into the educational environment [4], [5], in order to improve the effectiveness and quality of the education system [6]- [8]. This development also provides additional training and opportunities for students to explore their problemsolving attributes by seeking alternative solutions due to the unlimited computer use capabilities in the learning [9]- [11].…”
Section: Introductionmentioning
confidence: 99%
“…Di sisi lain, penggunaan VR dalam pembelajaran daring efektif meningkatkan motivasi belajar serta menumbuhkembangkan keterampilan peserta didik, utamanya dalam pembelajaran praktikum (Kustandi et al, 2020). Penggunaan VR mempermudah peserta didik dalam memahami materi (Prayudha et al, 2017).…”
Section: Pendahuluanunclassified
“…The authors have previously conducted research related to VR Use in Online Learning for Higher Education at Universitas Negeri Jakarta [24]. The results showed that students were motivated in the learning process.…”
Section: Self-regulated Learningmentioning
confidence: 99%